TEMPORAL CHARACTERISTICS AND CONTRADICTIONS OF STUDENT YOUTH - Polina A. Ambarova; Garold E. Zborovsky (Высшее образование в России)
Student youth is considered as a specific age community. Its development has inherent temporal characteristics and complex temporal contradictions. Among the temporal characteristics the authors mark out the extension of the age limits of student community, increasing the duration of educational activity, change of time budget. The paper shows how these characteristics affect the age parameters of students as a social community. In this connection the article reveals the author's understanding of age and age community. The problem is the discrepancy between students' biological, psychological and social time manifested in physical and sexual development, secondary employment, time use. The paper examines the influence of social factors on the dynamics of students' biological, psychological and social time.